Survey on various lane and driver detection techniques based on image processing for hilly terrain. Issue 9 (1st September 2018) - Manoharan, Kodeeswari; Daniel, Philemon
Abstract : As vehicular traffic continues to grow traffic management and prevention of accidents has become a major concern. This problem only gets magnified when travel on the mountainous roads are considered. This study is especially focused toward Himalayan mountains as they pose a greater risk because of their rugged natural setting. This study investigates crucial problems faced on the hilly roads and the challenges in translating existing driver‐assistance systems to such roads. The survey probes every lane detection algorithms, image processing techniques and various assistance features for applicability to hilly roads discussing the pros and cons for each of them. Conclusions are drawn as to deduce the more suitable methods that can be improvised and re‐tuned to adapt them for mountainous roads.